Aktivitas Anti Obesitas Ekstrak Daun Tin (Ficus carica Linn) pada Tikus yang diberi Diet Lemak Tinggi - Errol Rakhmad Noordam; Swasono R. Tamat; Syamsudin Abdillah (Fakultas Farmasi Universitas Pancasila, 2019)
Obesity is a health problem in the community because it can cause a risk of degenerative diseases such as type 2 diabetes mellitus, high blood pressure, heart disease, cancer, and atherosclerosis. Unhealthy lifestyles such as lack of physical activity by exercising, a diet high in carbohydrates and fats, can cause fat deposits in the body, especially in the abdomen. The use of chemical drugs such as Orlistat as a weight loss or to help reduce the risk of regaining lost weight, is less effective because it requires a long consumption time and the presence of side effects. Tin leaf content (Ficus carica Linn) is flavonoids, alkaloids, tannins and steroids, tin leaf extract has IC50 150mg/L antioxidant activity. This study was to determine the anti-obesity activity of tin leaf extract in male Sprague-Dawley rats given a high fat diet. 30 Sprague-Dawley rats were classified into 6 groups. The results obtained, in the group dose of 100 mg / kg obtained an average body weight of 381.8 grams, the test group 200 mg / kg obtained an average body weight of 414.5 grams, in the test group 400 mg / kg obtained 387 grams. The conclusion of this study is that the activity of Tin leaf extract (Ficus carica Linn) can be used as an anti-obesity.